Entrepreneurial Education and Africa’s Attainment of Sustainable Development Goals - Ngobese, Thanduyise; Beharry-Ramraj , Andrisha (Journal of Sustainable Development Law and Policy, 2025)
Entrepreneurship has the potential to reduce poverty, stimulate economic growth and boost innovation, in addition to enhancing social and environmental sustainability. In accordance with the human capital theory and previous empirical studies, it is assumed that entrepreneurship education and training directly correlate with positive entrepreneurial outcomes and therefore sustainable development. Although several scholars have attempted to review and analyse entrepreneurship education and training literature over the past decade, none of these reviews directly links entrepreneurship education and training with sustainable development or focuses on the role and status of entrepreneurship education and training (research) in less-stable areas of the world. This article analyses recent literature to identify the extent to which entrepreneurship education and training research addresses Sustainable Development Goals (SDGs). The review identifies several gaps in research and practice that potentially hinder entrepreneurship education and training from adequately advancing sustainable development, including a dearth of research on African states and demographic diversity, limited entrepreneurship education and training access to non-university students and a general lack of focus on educational technology, progressive education approaches, and innovation in African countries compared to stable ones. The review also identifies challenges pertaining to entrepreneurship education and training resource constraints in fragile contexts. The article concludes by offering insights on how educational technology could mitigate entrepreneurship education and training challenges in developing Africa environments to ultimately ease some barriers towards SDG advancement and provides recommendations for future research directions.